The Role of Translation in Cognitive Integration and the Promotion of the Arabic Language: A Perspective on Methods of Realizing Sciences between the Past and the Present - Si Mohammed Ayada, Amine (LANGUAGE ART, 2024)
This paper discusses the role of translation in achieving cognitive integration, which contributed to the construction and revival of Arabic sciences, making them effective and present in the civilizational building of neighboring nations. It also sheds light on the role of the Arabic language in transferring knowledge, considering it a significant means that contributes to expanding the circle of cognitive integration and its construction. The research topics address the ancient Arabs’ awareness of the necessity of cognitive integration and their adoption of their language as a bridge and a means of conveying the sciences they reached to neighboring countries. The translation of various sciences into the Arab and Islamic world would not have been achieved without the transfer of materials from the languages and cultures of ancient nations, such as Greek and Persian Pahlavi, and from the philosophy and sciences of India, into Arabic, and then from Arabic into Latin in the Middle Ages. Furthermore, many of the transferring scholars achieved cognitive integration in the sciences and knowledge they translated, so diverse sciences converged in many of them. We mention here among these Thabit ibn Qurra al-Harrani, the Arab translator scholar who was famous for his depth in astronomy, mathematics, geometry, and music, and who translated several works from Greek into Arabic. Here, it must be noted in fairness that many scholars who wrote in Arabic were from different races and societies. Indeed, most of them were Persians, and they wrote their scientific research in the Arabic tongue, as well as in their own (Persian) language; in research models, they worked on translation and authorship, transferring their works from their original languages to Arabic. Despite this, the vast majority of scientific works produced in the periods between the ninth and sixteenth centuries were written in the Arabic language by scholars who mastered multiple disciplines (what we call today a "polymath" or encyclopedic scholar). They explored various knowledge, identified what was suitable for transfer and the method thereof, facilitated the difficult and simplified the complex, thereby establishing the first building blocks of our subject on the role of translation in achieving cognitive integration between sciences.